DEVELOPMENT OF JOBSHEET-BASED E-MODULES IN FASHION BUSINESS MANAGEMENT COURSES - Hanim, Halida; Rahma Dewi, Eka (International Journal of Innovative Technologies in Social Science, 2024)
Limited time for the sewing process during learning is a significant obstacle, because you have to explain sewing procedures in theory and during practice. This causes students to not be able to absorb detailed and clear information on the steps for making clothing production. The aim is to 1) develop a module assisted by a job sheet and 2) a module suitable for use in learning, especially in fashion business management courses. The learning media for the module is assisted by job sheets using the research and development (R&D) method. The development model used is the Dick and Carey development model. Based on the assessment of material experts 93.9%, media experts 93%, small group student responses 68.6%, medium group 82.2% and trials in large groups 91% with the category very feasible so it can be used as learning media.